ألفاظ القوة والتمكين في سورة القمر " دراسة صوتية دلالية" - العمراتي, منصور (University of Eloued جامعة الوادي, 2020)
ملخص البحث. الباحث: د. منصور علي سالم ناصر العِمراني الدرجة العلمية: أستاذ مشارك التخصص: تفسير وعلوم القرآن عنوان البحث: ألفاظ القوة والتمكين في سورة القمر" دراسة صوتية دلالية. الهدف من البحث: يهدف هذا البحث إلى بيان صورة من صور الإعجاز القرآني وهو بيان الألفاظ القوية الرصينة ذات الجرس الصوتي القوي الرصين المتمكن، وعلاقتها ببيان معاني الآيات التي وردت فيها، ومدى تمكنها من قرارها في السياق الذي وردت فيه. هذه الألفاظ القوية عادة ما يكثر ورودها في السور المكية، كونها تتناول الموضوعات القوية كالعقيدة، وإثبات البعث والنشور، وبيان مصير الأمم المكذبة برسلها...الخ. وقد تناول هذا البحث الألفاظ القوية الشديدة التي وردت في سورة القمر مكية النزول، والتي احتوت على الكثير من الكلمات القرآنية القوية والرصينة من الناحية الصوتية، إما تبعا لصفات حروفها مثل (اقْتَرَبَتِ- مُزْدَجَرٌ- صَرْصَرًا- فَانْتَصِرْ- مُنْقَعِرٍ-وَاصْطَبِرْ...الخ) أو تبعا لغرابة الألفاظ الذي تفردت به هذه السورة دون غيرها من حيث الحركات، الحذف من اللفظ، البناء للمجهول مثل: (وَنُذُرِ- أَشِرٌ- وَدُسُرٍ –كُفِرَ- مُحْتَضَرٌ الْمُحْتَظِرِ...الخ) مكونات البحث. يتكون هذا البحث من: المقدمة:وفيها أسباب اختيار الموضوع، ومشكلته، وحدوده، وهدفه، ومنهج البحث، وطريقته. المبحث الأول: مفهوم ألفاظ القوة والتمكين . وفيه ثلاثة مطالب: المطلب الأول: مفهوم اللفظ في اللغة والاصطلاح. المطلب الثاني: مفهوم القوة في اللغة والاصطلاح. المطلب الثالث: مفهوم التمكين في اللغة والاصطلاح. المبحث الثاني: ألفاظ القوة والتمكين في سورة القمر. وفيه مطلبان: المطلب الأول: التعريف بسورة القمر. المطلب الثاني: الدراسة الصوتية الدلالية لألفاظ القوة والتمكين من خلال آيات سورة القمر. الخاتمة: وفيها أهم النتائج والتوصيات. Abstract Researcher: Prof. Dr. Mansoor Ali Salem Nasser Al-Emrani (Associate Professor), Interpretation and Qur'an sciences Title: “The Words of Power and Empowerment in Surat Al-Qamar: An Audio-Semantic Study.” Objective of the Study: This research aims to investigate a form of the Qur’anic miracle. The study reveals strong and powerful words with unique voices that contribute to the power of statements as larger units (verses). The harmony between the nature of the sounds and theme reflect the strong relationship between the topic and the context and how this clarifies the meanings of the verses contained therein. These indicative and strong words are frequently mentioned in the Meccan Surahs, as they deal with strong issues such as belief, proof of resurrection, and clarify the fate of the nations who falsified their messengers ... etc. Hence, this research deals with the robust and strong words that appeared in Surat Al-Qamar, as Meccan Surah, which contains several strong sounds of Quranic words from the audio-vocal perspective, either according to the characteristics of the letters used such as (اقْتَرَبَتِ) approaching, (مُزْدَجَرٌ) deterrence, (صَرْصَرًا) furious wind, (فَانْتَصِر) so help, (مُنْقَعِر) uprooted, (وَاصْطَبِرْ) and be patient, etc., or, through the strangeness of the words in which this Surah is unique in terms of semantics, sound deletion from the word, and the use of passive voice forms such as (وَنُذُر) being warned, (أَشِر) to be insolent, (وَدُسُرٍ), being nailed (كُفِر) to be disbelieving, (مٌحْتَضَر) being moribund, (الْمُحْتَظِرِ) a fence builder of animal farms. Research Contents This research consists of two chapters with an introduction and a conclusion. Introduction: This section sheds some light on the research objectives, research problem, research limitation, and the reach methodology. The research has been divided into the following chapters and sub-chapters. The First Chapter includes the concept of words strength and empowerment. It consists of three sections: The first section includes the concept of pronunciation in terms of language and terminology. The second section deals with the concept of power in language and Quranic Terms. The third Section focuses on the concept of empowerment in language and terminology. The Second Chapter focuses on words strength and empowerment in Surat Al-Qamar. It consists of two sections: The first section defines Surat Al-Qamar. The second Section has been devoted for the audios and semantics of the words power and empowerment through Surat Al-Qamar. Conclusion contains the most important findings and recommendations. الكلمات المفتاحية
مقال
Keywords: ألفاظ ; الق ; ة ; - التمكين ; دراسة ; ص ; تية ; دلالية